Greening our working lives: the environmental impacts of changing patterns of paid work in the UK and the Netherlands, and implications for working time policy - Pullinger, Martin Iain (The University of Edinburgh, 2012)
Paid working patterns are currently regulated by governments around the world for a range of social and economic reasons: to increase labour supply and skills; to provide a strong tax base to support an ageing population; to help people reconcile work and family life over increasingly diversified life courses; and to be in line with the general principle of the activating, employment led welfare state. Environmental considerations rarely feature in the design or evaluation of working time policy. Nevertheless, various authors working on policies for sustainable development argue that reductions in average paid working time could lead to environmental benefits: as people work less, they in turn earn less, and so consume less, resulting in lower environmental impacts from lower levels of production of products. This thesis takes this argument as its starting point, and synthesises these distinct perspectives on working time and its regulation to address two key questions: what level of environmental benefits could arise from such reductions in paid working time?; and what are the implications for the design of working time policy? The research addresses these questions, taking the case of greenhouse gas emissions, and the UK and the Netherlands in the early 2000s as case studies. Using household expenditure survey data and data on product emissions intensities, the relationship between paid working time and emissions is analysed at both the household and national levels. At the household level, statistically and substantively significant correlations are found between higher levels of paid work and higher levels of consumption and so greenhouse gas emissions. The effects on emissions of hypothetical changes in the working patterns of the national populations are then modelled. The research estimates that meeting current national objectives to increase labour market participation rates would increase national greenhouse gas emissions by 0.6-0.7%, a cost that might be considered acceptable if it also achieves its aims of reducing income poverty, benefit dependency, and social exclusion. Meanwhile, widespread reductions in average working hours and increased use of career breaks, with corresponding reductions in income, would reduce national emissions. The scenarios modelled (a 20% reduction in the working hours of full time workers, and increasing use of 3 month career breaks) lead to reductions of 3-4.5% in national emissions, with the corresponding increases in “leisure” time, reductions in income inequality, and reduced gender imbalances in the distribution of paid work potentially also improving wellbeing, social cohesion, and gender equality in work and care. The results indicate that environmental factors warrant consideration in the design and evaluation of working time policy, and that challenging but achievable levels of working time reduction could contribute a small but significant share to meeting greenhouse gas emissions targets. Policy instruments would need to address a range of values, attitudes and norms around employment and consumption, as well as employer and situational factors, if substantial working time reduction were to be achieved. Reconciling diverse environmental, social and economic goals also requires careful policy design, particularly for certain demographic groups such as the low income, who would need financial and other support to turn rights to reduce working time into functional freedoms that they could utilise.
Keywords: working time reduction; carbon footprint; scenario modelling; working time policy